2019
DOI: 10.1016/j.jvs.2019.01.053
|View full text |Cite
|
Sign up to set email alerts
|

The 10-year outcomes of a regional abdominal aortic aneurysm screening program

Abstract: Objective: In 2007, Medicare established ultrasound screening guidelines to identify patients at risk for abdominal aortic aneurysm (AAA). The purpose of this study was to evaluate AAA diagnosis rates and compliance with screening during 10 years (2007-2016) of the Screen for Abdominal Aortic Aneurysms Very Efficiently Act implementation within a regional health care system. Methods: A retrospective chart review of all patients screened for AAA from 2007 to 2016 within a regional Veterans Affairs health care s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…In these guidelines a slight decrease of aneurysm prevalence has been described probably caused by change in smoking habits. This is supported by the results from a recent publication [2]. In this retrospective study, the 10-year outcomes of an abdominal aortic aneurysm (AAA) screening program by a regional Veterans Affairs health care system was evaluated.…”
Section: Epidemiologymentioning
confidence: 85%
“…In these guidelines a slight decrease of aneurysm prevalence has been described probably caused by change in smoking habits. This is supported by the results from a recent publication [2]. In this retrospective study, the 10-year outcomes of an abdominal aortic aneurysm (AAA) screening program by a regional Veterans Affairs health care system was evaluated.…”
Section: Epidemiologymentioning
confidence: 85%
“…Confirming this trend, the 10-year outcome evaluation of the American veterans’ AAA screening program reported fewer large AAAs had been detected in the last 5 years of the study, and overall, more but smaller (3.0–4.4 cm) aneurysms were being detected. In addition, the 10-year rate of AAA diagnosis had declined from 7.2% to 6.3% in the first 5 years with patients expected to outlive their predicted 11-year life expectancy ( Chun et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“… McCaul et al (2016) concluded that screening men aged 65–74 years old for AAA was ineffective because AAA mortality was not significantly reduced, due to lower than expected AAA mortality rates in a cohort of non-screened men. Related to this issue, Chun et al (2019) predicted that because more men were being detected with smaller AAAs at younger ages, increased annual surveillance would likely burden health institutions in the United States. Furthermore, Johansson et al (2018) doubted the benefits of an AAA screening program, as decreasing rates of rAAA and AAA mortality were seen in the older adult male population, regardless of screening.…”
Section: Resultsmentioning
confidence: 99%
“… 9 , 16 In the United States, one-time screening for AAA has been offered since 2007 to male members of Medicare between the ages of 65 to 75 years with any history of smoking. 17 …”
Section: Introductionmentioning
confidence: 99%
“…9,16 In the United States, one-time screening for AAA has been offered since 2007 to male members of Medicare between the ages of 65 to 75 years with any history of smoking. 17 In Sweden, the prevalence of AAA in 65-year-old men is 1.5%. 9 The national screening program in the United Kingdom has shown a AAA prevalence in ≥65-year-old men at 1.57%.…”
Section: Introductionmentioning
confidence: 99%